Estudantes do Ensino Superior: variáveis pessoais e contextuais relacionadas ao insucesso acadêmico e evasão escolar - Faria, Ana Amália Gomes de Barros Torres (2022)
Over the past few decades, research around adaptation and academic success in higher education has increased. A greater number and diversity of students enter this level of education, justifying greater concerns about their academic performance and consequent completion of training. Data collection took place longitudinally at the Instituto Federal de Alagoas-Ifal (Campus Maceió) and included three studies with different samples, between 317 and 420 students from different courses, distributed between degrees or bachelors. At first, even before the pandemic, we applied the questionnaires in person. Subsequently, with the Covid-19 pandemic and the transition of activities to Emergency Remote Teaching (ERE), all the research was done from contacts and the application of online questionnaires. The study considered the following steps: the first took place at the time of enrollment, between the 1st and 3rd week after admission, where students were invited to participate in the study and provide information regarding sociodemographic characteristics; your previous academic career; as well as expectations and anticipated difficulties related to the chosen course. The second stage took place between the 6th and 8th week of classes since the beginning of the course. In this phase, information related to the academic experiences of these students was collected; and inserted questions about the socio-emotional impact of the Covid-19 pandemic. In the third stage, at the end of the school year, the process of adapting students to their courses and their intention to drop out of the course was evaluated. The thesis compiles four articles, including an introduction, a theoretical reference chapter and methodological course and a conclusion. The articles that made up the thesis were: 1- “Academic Adaptation of 1st Year Students: Promoting Success and Permanence at the University”; 2- “Academic Expectations and Difficulties in Higher Education Entrants: Analysis in Function of Gender and Quota System”; 3- “Effects of Remote Learning on Higher Education students”; 4-"Difficulties in the academic adaptation of higher education students in times of a pandemic". The results point to the complexity of the convergence of personal and contextual variables in the process of academic success and school dropout. In this process, the need for public policies to gradually decrease the retention and dropout rates stands out, as well as the design of institutional strategies to support the career development of these students, mainly through integration activities and support services. specialized.